2015
DOI: 10.3892/or.2015.3755
|View full text |Cite
|
Sign up to set email alerts
|

Maslinic acid potentiates the antitumor activities of gemcitabine in vitro and in vivo by inhibiting NF-κB-mediated survival signaling pathways in human gallbladder cancer cells

Abstract: Abstract. Gemcitabine (GEM) is one of the first-line drugs in the treatment of gallbladder cancer (GBC), although the therapeutic effect is not sustained due to resistance to the drug over time. Maslinic acid (MA) has been shown to inhibit transcription factor nuclear factor-κB (NF-κB), resulting in the suppression of survival signaling. The authors of the present study investigated whether MA enhanced the antitumor activity of GEM in GBC. Anti-proliferative effects of MA, GEM and MA + GEM were assessed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Gemcitabine has been shown to suppress cancer migration and invasion by altering MMP-2 expression and EMT protein levels [54] , [55] , [56] , [57] , [58] . We found that gemcitabine alone could decrease expression of MMP-2, vimentin and snail as well as increase expression of E-cadherin ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Gemcitabine has been shown to suppress cancer migration and invasion by altering MMP-2 expression and EMT protein levels [54] , [55] , [56] , [57] , [58] . We found that gemcitabine alone could decrease expression of MMP-2, vimentin and snail as well as increase expression of E-cadherin ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in one or a few genes remain crucial for maintaining drug resistance cell survival and malignant phenotype. There is evidence to indicate that NF-κB, 20 , 21 , 22 , 23 AKT, 20 , 24 , 25 MAPK, 25 , 26 HIF-1α 27 pathways are involved in gemcitabine resistance in vitro and some in vivo models ( Fig. 1 ).…”
Section: Known Mechanisms Of Gemcitabine Resistancementioning
confidence: 99%
“…Existing evidence has revealed that MA exerts therapeutic effect on a wide variety of human solid tumors, including hepatocellular carcinoma (Ku et al, 2015), colorectal carcinoma (Yoo et al, 2015), gastric carcinoma (Lee et al, 2015), and breast carcinoma (Alam and Khan, 2017). Moreover, MA has been shown to potentiate the anti-tumor activity of conventional chemotherapeutic drugs or reverse chemoresistance of cancer cells to conventional chemotherapeutic drugs (Yu et al, 2015). In this study, we found that MA cotreatment could significantly reverse DOC resistance in human docetaxel-resistant breast carcinoma MDA-MB-231 cells via enhancing cellular DOC accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-cancer effect of MA has been confirmed in multiple types of human cancers including TNBC (Reyes-Zurita et al, 2009;Li et al, 2010;Lin et al, 2014;Parikh et al, 2014). Yu et al have reported that MA can enhance the anti-tumor effect of gemcitabine in gallbladder cancer cancer cells by inhibiting transcription factor nuclear factor-kappa B (Yu et al, 2015). Villar et al have reported that MA sensitizes soft tissue sarcoma cells to DOC by inhibiting the multidrug resistance protein MRP-1 (Villar et al, 2014).…”
Section: Introductionmentioning
confidence: 98%